Representation of Woman in the movie “Girl in the Box": Violence against Woman Theory - Ainiyah, Syaifah; Yusuf, Faidah; Barsihannor, Barsihannor (Journal of Islamic Culture and Literature (JICeL), 2020)
This article is about Representation of Woman in the movie “Girl in the Box”: Violence against Woman Theory. The researcher used a descriptive qualitative analysis of violence against women from Linda Bickerstaff, which is analyzing a scene of dialogue and image. This study has shown that girl in the box presents women as the leading character who dealt with injustice. The results of analysis of women have been represented as weak and defenseless women to be the victims of physical, emotional, sexual, psychological and economical violence: spreading fear, assaults on physical action, threats, coercion of sexual relations, sexual abuse, and a sense of helplessness and a lack of confidence. This study led to the conclusion that women were pandered to as exploiting women and women’s lib rates. Women tend to be yielding, weak, cry, and dominate men.